Systemic disease in leukocytoclastic vasculitis: a focus on direct immunofluorescence findings - Sümeyre Seda Ertekin; Ayşe Esra Koku Aksu; Cem Leblebici; Vefa Aslı Erdemir; Ozan Erdem; Elif Bal Avcı; Mehmet Salih Gürel (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Direct immunofluorescence (DIF) panels are usually ordered for clinically suspected cutaneous vasculitis, but their positivity rate is variable, and their prognostic significance is not clear to date. Objective The study aims to investigate the systemic involvement rate in leukocytoclastic vasculitis (LCV) patients and the potential clinical and laboratory associations with systemic involvement, including DIF findings. Methods A retrospective study of patients with histopathologically proven cutaneous LCV examined in the dermatology department between 2013 and 2017 was performed. Results Of the 81 patients (mean age, 50.6 years), 42 (52%) were male. The mean time between the appearance of skin lesions and biopsy was 23.1 days, ranging from 2 to 180 days. DIF showed overall positivity of 90.1%, and C3 was the most frequent immunoreactant (82.7%). Any kind of extracutaneous involvement was present in 47 (58%) of patients, with renal involvement being the most frequent (53.1%), followed by articular (18.5%) and gastrointestinal (11.1%) involvement. The presence of renal disease was associated with the detection of IgG in the lesional skin (p = 0.017), and with the absence of IgM in the lesional skin (p = 0.032). There was a significant association between C3 deposition and joint involvement (p = 0.05). Study limitations This is a single-center study with a retrospective design. Conclusion DIF seems to be a useful ancillary diagnostic tool in the evaluation of cutaneous vasculitis, but the relationship between DIF findings and systemic involvement needs to be further elucidated due to contradictory data in the current literature.